Review of climate screening approaches and tools for agricultural investment: Areas for action and opportunities to add value - Brown, Douglas R. (2017)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Climate Risk Management Flagship aims to enable the transition towards more climate-smart agricultural systems and climate-resilient rural livelihoods in high-risk environments. It does this in part by supporting the availability and effective use of relevant climate information by farmers and by the institutions that support them. As an initial step towards assessing whether and how CCAFS and its partners might contribute to improvements in the ways these funds are screened and used, CCAFS commissioned this selective review of current climate screening approaches and tools that several major development investors have put in place in recent years, focusing on their approach to screening investments in agriculture and food security. This selective review of donor agencies was undertaken in order to understand their various approaches to climate screening, identify current issues that they are facing, look for common threads and themes among them and suggest ways in which CCAFS might add value to their screening processes and that of other donors.